The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1088/0004-637x/814/1/39
|View full text |Cite|
|
Sign up to set email alerts
|

EXCITATION MECHANISMS FOR HCN(1–0) AND HCO+(1–0) IN GALAXIES FROM THE GREAT OBSERVATORIES ALL-SKY LIRG SURVEY*

Abstract: For L IR - The best-fit lines in Figure 6 of the original article are correct and the conclusions of the paper are not affected. We thank Iván Oteo for bringing the discrepancy in the original paper to our attention. , and J HNC 1 0 ( ) =  , for a sample of 58 local luminous and ultraluminous infrared galaxies from the Great Observatories All-sky LIRG Survey (GOALS). By combining our new IRAM data with literature data and Spitzer/IRS spectroscopy, we study the correspondence between these putative tracers o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
97
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(116 citation statements)
references
References 53 publications
(102 reference statements)
15
97
1
Order By: Relevance
“…Assuming a fundamental relationship between the amount of dense gas and the star formation rate exists, then scatter in the relationship between the HCN 1-0 intensity and the actual amount of dense gas would contribute to the observed scatter in the GaoSolomon relationship. Our identification of HCN abundance variations and self absorption as sources of this scatter could help explain the increased scatter and systematic deviations seen when testing the Gao Solomon relationship for larger samples of more extreme sources, including ULIRGs (Privon et al 2015) and AGN (Davies et al 2012;Imanishi et al 2009;Kohno et al 2003). Wu et al (2005) interpret the Gao-Solomon relationship as indicating that individual, sub-parsec scale dense cores are the fundamental unit of dense gas mass associated with star formation, and that the Gao Solomon relation on larger scales is essentially counting the number of these structures.…”
Section: The Interpretation Of the Gao-solomon Relationmentioning
confidence: 92%
See 1 more Smart Citation
“…Assuming a fundamental relationship between the amount of dense gas and the star formation rate exists, then scatter in the relationship between the HCN 1-0 intensity and the actual amount of dense gas would contribute to the observed scatter in the GaoSolomon relationship. Our identification of HCN abundance variations and self absorption as sources of this scatter could help explain the increased scatter and systematic deviations seen when testing the Gao Solomon relationship for larger samples of more extreme sources, including ULIRGs (Privon et al 2015) and AGN (Davies et al 2012;Imanishi et al 2009;Kohno et al 2003). Wu et al (2005) interpret the Gao-Solomon relationship as indicating that individual, sub-parsec scale dense cores are the fundamental unit of dense gas mass associated with star formation, and that the Gao Solomon relation on larger scales is essentially counting the number of these structures.…”
Section: The Interpretation Of the Gao-solomon Relationmentioning
confidence: 92%
“…HCN 1-0 is observed to be anomalously bright in active galactic nuclei (AGN), compared to CO and HCO + (Davies et al 2012;Imanishi et al 2009;Kohno et al 2003). Graciá-Carpio et al (2006) also find that HCN 1-0 may be overluminous compared to HCO + in ultraluminous infrared galaxies (ULIRGs), and Privon et al (2015) also find that overluminous HCN 1-0 is not limited to galaxies containing AGN. In addition to these indications that HCN 1-0 is overluminous in some environments, there are observations that a single power-law spectrum is insufficient to describe both normal galaxies and ULIRGs.…”
Section: Introductionmentioning
confidence: 93%
“…Privon et al (2015) have shown that some pure starburst and composite sources show similarly enhanced HCN emission. The origin of this enhancement is uncertain, but might be due to mid-infrared pumping associated with a compact obscured nucleus (CON; e.g., Aalto et al 2015).…”
Section: Optical and Radio Emissionmentioning
confidence: 97%
“…Recently the favored scenario for the enhancement of HCN around AGNs in observational data is high temperature chemistry likely due to mechanical heating (Harada et al 2010;Izumi et al 2013;Matsushita et al 2015). The increasing number of sources detected in these species seem to show in average an enhancement of the HCN/HCO + ratio in the presence of an AGN (Privon et al 2015;Izumi et al 2016;Imanishi et al 2016). However, the scatter is large among the ratios observed in both galaxies hosting AGNs and starbursts (Privon et al 2015), which makes it necessary to study individual cases at high resolution to understand the origin of such dispersion.…”
Section: Hcn/hcomentioning
confidence: 99%
“…The increasing number of sources detected in these species seem to show in average an enhancement of the HCN/HCO + ratio in the presence of an AGN (Privon et al 2015;Izumi et al 2016;Imanishi et al 2016). However, the scatter is large among the ratios observed in both galaxies hosting AGNs and starbursts (Privon et al 2015), which makes it necessary to study individual cases at high resolution to understand the origin of such dispersion. In addition, recent high resolution observations with ALMA have shown that this enhancement may occur in the surroundings and not towards the AGN itself (García-Burillo et al 2014;Martín et al 2015;Izumi et al 2016).…”
Section: Hcn/hcomentioning
confidence: 99%